Tufted angioma arising at the site of hepatitis B vaccination: A case report - Mozhdeh Sepaskhah; Jalal Hajizadeh; Fatemeh Sari-Aslani; Farideh Jowkar (The Turkish Journal of Pediatrics)
Tufted angioma is a benign vascular proliferation which presents most commonly in infants and children and could occasionally be complicated by Kasabach-Merritt syndrome. Here, we report a 4-month-old girl with erythematous firm plaque on left thigh at the site of hepatitis B vaccine injection accompanied with thrombocytopenia. Histological examination showed multiple lobules of capillary sized vascular proliferation in the dermis and subcutaneous fat (cannonball appearance) with dilated thin walled vascular channels at the periphery of the lobules. According to our search this patient is the second case of tufted angioma arising at the site of vaccination.